1980
DOI: 10.1037/0096-1523.6.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Foveal metacontrast: I. Criterion content and practice effects.

Abstract: Strong metacontrast was found during experiments involving foveal presentation of stimuli. Follow-up experiments indicate that foveal metacontrast can be accounted for in some conditions by a practice effect and/or a criterion-content change, which occurs with practice and involves a biphasic brightness response to the target. Consideration of these factors may help resolve some of the many apparent disparities in the metacontrast literature. The relevance of these factors to metacontrast theories is discussed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 32 publications
1
39
2
Order By: Relevance
“…Psychophysical data, however, show metacontrast to be more complex than either the models and theories cited above or the electrophysiological correlates would imply. An effect that none of the present models can explain with their proposed neural interactions is the near disappearance of metacontrast with enough practice (Ventura, 1980). Vttal (1971) gives other, more general reasons why current neurophysiological models are unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychophysical data, however, show metacontrast to be more complex than either the models and theories cited above or the electrophysiological correlates would imply. An effect that none of the present models can explain with their proposed neural interactions is the near disappearance of metacontrast with enough practice (Ventura, 1980). Vttal (1971) gives other, more general reasons why current neurophysiological models are unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper on electrophysiological correlates of metacontrast showed no YEP correlates of metacontrast in a "C1" component that reflected activity of striate cortex (Jeffreys & Musselwhite, 1986). However, while C1 is an early potential that reflects afferent activity, extensive evidence, much of it published in Perception & Psychophysics, has shown metacontrast to be a complex phenomenon that is influenced by repetition, practice, binocularity, and other effects to be expected at a higher level (Schiller & Greenfield, 1969;Schiller & Smith, 1968;Ventura, 1980;Weisstein, 1971). Thus, we would expect correlates of metacontrast in laterVEP components, where higher level influences can be seen.…”
mentioning
confidence: 99%
“…Nonetheless, dealing with an unusual finding such as below-chance performance calls for caution. Nonmonotone masking functions might not reflect nonmonotone changes in sensitivity, and it is possible that sufficient practice might eliminate the masking (Bernstein, Proctor, Proctor, & Schurman, 1973;Hogben & Di Lollo, 1984;Schwiedrzik, Singer, & Melloni, 2009;Ventura, 1980;Wolford, Marchak, & Hughes, 1988). We used extensive training to eliminate practice effects and a rating procedure to estimate each observer's sensitivity as measured by his ROC.…”
Section: Experiments 2: Foveal and Parafoveal Sensitivity (D′)mentioning
confidence: 99%
“…Ventura (1980) found that severity of metacontrast masking decreased dramatically over successive experimental sessions. In view of this result, the question arises as to whether perception of the first stimulus improves with practice in an apparent motion paradigm as well in metacontrast.…”
mentioning
confidence: 98%